Stakeholders’ views on the advantages and disadvantages of using English as a language of instruction (ELoI) for vocational education and training (VET) in Tanzania - Mgoge, Mwita; Kahangwa, George; Abdala, Jafari (Papers in Education and Development, 2024)
Drawing on a multiple-case study design involving semi-structured interviews and focus group discussions, this research investigated the perspectives of 32 stakeholders from two centres in the Dar es Salaam and Arusha regions on the benefits and drawbacks of using English as the language of instruction (ELoI) in Vocational Education and Training (VET). The results indicate that using ELoI enhances access to employment opportunities, provides abundant teaching and learning resources, improves English language communication skills, enriches vocabulary, boosts speaking confidence, and supports technical and professional functions. However, it also reinforces social stratification, hinders student achievement, limits creativity, and consumes instructional time. To support the effective implementation of ELoI, recommended measures include introducing an intensive communicative English programme for students with low proficiency and permitting code-switching between English and Kiswahili in VET classrooms.